Pengaruh Konten dan Visualisasi Laman terhadap Minat Baca dengan Moderasi Iklan Pop-Up - Nova Lidarni; Novita Sari (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to determine the influence of content information and page visualization on interest reading with pop-up ads as moderation in consumers who access Lampost.co pages. Methodology/approach: This study uses a quantitative approach with primary data sources. The sampling technique used was probability sampling, and the number of samples was 200. Data were collected by distributing questionnaires and processed using Smart PLS.  Results/findings: The results of the study were that the content information variable had an effect on the interest reading variable, the page visualization variable had an effect on the interest reading variable, pop-up ads strengthened the influence of content information had an effect on the reading interest variable, and the pop-up ad weakened the influence of page visualization on the reading behavior variable. Conclusions: This study concludes that content and page visualization significantly influence reading interest, whereas pop-up ads do not strengthen this effect. Limitations: This study only focuses on consumers who access Lampost.co pages in Bandar Lampung. Further research should use a wider sample so that the results are more generalizable. Contribution: Lampost.co can improve content information and page visualization so that consumers are more aware of updated information and giving rise to reading behavior is encouraged.